Translation of Emotional Media From English to Russian - NASIBULLOVA, Guzel Rishatovna; MURZABEKOV, Meirambek Kazbekovich (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The emotional sphere is considered one of the most complex human systems. The modern translator of literary texts has a double task: to convey the realities and images characteristic of the culture of the original language and, at the same time, preserve the integrity, clarity and harmony of the native language. The practical value of the study is to determined the possibility of applying the results contained in the practice of artistic translation, in teaching the methodology of translation, in the development of didactic manuals an in the teaching of english. RESUMEN La esfera emocional se considera uno de los sistemas humanos más complejos. El traductor moderno de textos literarios tiene una doble tarea: transmitir las realidades e imágenes características de la cultura del idioma original y, al mismo tiempo, preservar la integridad, la claridad y la armonía del idioma nativo. El valor práctico del estudio está determinado por la posibilidad de aplicar los resultados contenidos en la práctica de la traducción artística, en enseñar la metodología de traducción en el desarrollo de manuales didácticos y en la enseñanza del inglés.